TRACING THE PATH TO DIAGNOSIS: INITIAL SYMPTOMS AND DELAYS IN SYSTEMIC SCLEROSIS FROM THETURKISH NATIONAL REGISTRY - Guler, A. Avanoglu; Baltaci, M. A.; Yazgan, B. Firlatan; Okyar, B.; Avcu, A.; Ugurlu, Z.; Akdogan, A. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Rare/orphan diseases; Descriptive Studies